Aarhus mod Herning: En samtale om fans, fodbold og forestillinger - Ejgod Hansen, Louise (Peripeti, 2012)
The article presents an analysis of four ’Theatre talks’ (focus group interviews) conducted in Aarhus and Herning about the performance Hvid Stolthed (Svalegangen, Aarhus). The main focus is on how the references in the performance to the local football milieu in Aarhus influence the experience of the different groups depended on their relation to and engagement in that milieu.